THU0325 Secukinumab demonstrates a consistent safety profile with up to 5 years treatment in patients with psoriatic arthritis and moderate to severe plaque psoriasis: updated pooled safety analyses. (12th June 2018) - Mease, P.J.; McInnes, I.B.; Reich, K.; Nash, P.; Widmer, A.; Abrams, K.; Pricop, L.; Fox, T.
Abstract : Background: Pooled safety data from secukinumab (SEC) studies in psoriasis and psoriatic arthritis (PsA) have been reported previously. 1 Objectives: To report updated longer-term safety data with up to 5 years of SEC treatment from psoriasis and PsA studies. Methods: The moderate to severe plaque psoriasis and active PsA data pool consisted of 15 and 3 Phase III studies, respectively. Different SEC doses in the studies included intravenous (up to 10 mg/kg) or subcutaneous (s.c.; 75–300 mg) loading, followed by s.c. maintenance dosing (300, 150 or 75 mg). Placebo patients were re-randomised to SEC at 12–24 weeks depending on study design. Adverse events (AEs) were reported as exposure adjusted incident rates (EAIR) per 100 patient-years and analyses included all patients who received ≥1 dose of SEC. Results: A total of 5181 and 1380 patients from psoriasis and PsA studies representing an exposure of 10416.9 and 3866.9 patient years, respectively, were included in this study. The most frequently reported AE was viral upper respiratory tract infection (table 1). EAIRs for serious infections, Candida infections, inflammatory bowel disease (IBD) and major adverse cardiac events (MACE) were low and similar in both psoriasis and PsA indications (table 1). No cases of tuberculosis were reported. Conclusions: SEC demonstrated a favourable safety profile during long-term treatment (up to 5 years) in patients with moderate to severe plaque psoriasis or PsA, hence, supporting long-term use. The safety profile was consistent with previous reports and comparable across psoriasis and PsA patients. Reference: [1] Mease, et al. Arthritis Rheumatol2017; 69(suppl 10):A606. Disclosure of Interest: P. Mease Grant/research support from: AbbVie, Amgen, BMS, Janssen, Lilly, Novartis, Pfizer, and UCB, Consultant for: AbbVie, Amgen, BMS, Celgene, Janssen, Lilly, Merck, Novartis, Pfizer, SUN Pharma, UCB, , Speakers bureau: AbbVie, Amgen, BMS, Janssen, Lilly, Pfizer, and UCB, I. McInnes Grant/research support from: AbbVie, Amgen, BMS, Celgene, Janssen, Lilly, Novartis, Pfizer, and UCB, Consultant for: AbbVie, Amgen, BMS, Celgene, Janssen, Lilly, Novartis, Pfizer, and UCB, Speakers bureau: AbbVie, Amgen, BMS, Celgene, Janssen, Lilly, Novartis, Pfizer, and UCB, K. Reich Consultant for: Abbvie, Affibody, Amgen, Biogen, Boehringer Ingelheim Pharma, Celgene, Centocor, Covagen, Forward Pharma, GlaxoSmithKline, Janssen-Cilag, Leo, Lilly, Medac, Merck Sharp and Dohme Corp., Novartis, Ocean Pharma, Pfizer, Regeneron, Sanofi, Takeda, UCB Pharma, Xenoport, Speakers bureau: Abbvie, Affibody, Amgen, Biogen, Boehringer Ingelheim Pharma, Celgene, Centocor, Covagen, Forward Pharma, GlaxoSmithKline, Janssen-Cilag, Leo, Lilly, Medac, Merck Sharp and Dohme Corp., Novartis, Ocean Pharma, Pfizer, Regeneron, Sanofi, Takeda, UCB Pharma, Xenoport., P. Nash Grant/research support from: AbbVie, Amgen, BMS, Celgene, Eli Lilly, Hospira, MSD, Pfizer, Janssen, UCB, Novartis, Roche, Consultant for: AbbVie, Amgen, BMS, Celgene, Eli Lilly, Hospira, MSD, Pfizer, Janssen, UCB, Novartis, Roche, Speakers bureau: AbbVie, Amgen, BMS, Celgene, Eli Lilly, Hospira, MSD, Pfizer, Janssen, UCB, Novartis, Roche, A. Widmer Shareholder of: Novartis Stock, Employee of: Novartis, K. Abrams Shareholder of: Novartis Stock, Employee of: Novartis, L. Pricop Shareholder of: Novartis Stock, Employee of: Novartis, T. Fox Shareholder of: Novartis Stock, Employee of: Novartis